Women Sharing Sacred Space: Multiple Religious Belonging and Gendered Rituals around La Divina Pastora - Syriac, Sharon (Religion & gender, 2026)
Based on ethnographic research, the article examines gendered ritual practice in Marian devotions in Trinidad and Tobago, where several religious traditions have met in the same pilgrimage site of La Divina Pastora since the late 19th century. The analysis focuses on the rituals of female pilgrims and custodians who share sacred space with people from different religious groups, including Hindu, Orisha, Pentecostal, and Roman Catholic denominations. Some of the pilgrims claim multiple simultaneous religious belonging. The article examines how Catholic women, as practitioners and custodians who perform key roles in the care, maintenance and devotions to La Divina Pastora, operate between and within these religious cultures.